Research status and challenges of waste heat thermoelectric generation for engines - ZHENG Youqu; YING Jie; LI Guoneng*; ZHU Yiyuan; SHEN Rong; TANG Yuanjun; GUO Wenwen (能源环境保护)
Energy conservation is one of the most important and economical ways to achieve the targets of Carbon Emissions Peak and Carbon Neutrality in our country. Waste heat is largely discharged into the environment during the engine operation resulting in the low engine working efficiency. The technology of semiconductor thermoelectric generation based on the Seebeck effect has great advantages in waste heat utilization from engines, which has been attracting extensive and intensive researches. This study introduces the working principle of thermoelectric generation, the device structure, and the components of the thermoelectric generation system. A review of thermoelectric generation research at home and abroad is also presented, in which the R&D status, application potential, evaluation metrics, and current challenges of thermoelectric materials and systems are analyzed. Several key scientific problems that affect the performance of the waste heat thermoelectric generation system, including thermoelectric efficiency and overall power generation efficiency, are proposed, and the corresponding preliminary solutions are given. The non-uniformity of the hot-end temperature distribution is one of the essential problems to design a high-performance waste heat thermoelectric generation system. In addition, the inherent contradictory between heat collection efficiency of the heat collector and pressure drop should be balanced to achieve the maximum fuel saving rate. Besides, new issues and data in application demonstration project of engine waste heat utilization have been presented to provide a useful guidance for future studies.